PHYTOCHEMICAL AND PHARMACOLOGICAL STUDIES OF ABUTILON BIDENTATUM HOCHST - Tripathi, Rekha (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present study deals with the phytochemical and Biological investigation of ethanolic extract of aerial parts of Abutilon bitentatum Hochst. Methods: Ethanolic extract of aerial parts of A. bitentatum was chromatographed over a silica gel column for phytochemical analysis and Pharmacological studies includes the anti-microbial, anti-viral and anti-tumor activity of ethanolic extract of aerial parts of A. bidentatum. Results: Phytochemical analysis of aerial parts of A. bitentatum revealed the presence of n-tetracosane, cetyl stearate, tetracosyl alcohol, cycloartenone, Î²-amyrin, Î²-sitisterol, alantolactone, isoalantolactone and a new cholestane derivative. The ethanolic extract of aerial parts of this plant showed trace activity for test bacteria and viruses but it is quite active against test fungi. Conclusion: The extract exhibited significant fungicidal activity.